Population dynamics of cestode parasite in Trygon zugei from Ratnagiri district (M.S.), India - Sunita Borde, *Sandeep Anarse, Sushil Jawale and (International Multidisciplinary Research Journal, 2011)
The present communication deals with the population dynamics of cestode parasite in Trygon zugei from different places of Ratnagiri District. (M. S.) India during the period of June 2009 to May 2010.Total 212 cestode parasites were recorded from 360 fishes. The collected parasites were of one genera i.e. Tetragonocephalum Shipley, [6]. This report summarizes the data incidence, intensity, density and index of infection of cestode parasites with effect of environmental factor.